Phagocytic function in cyclists: correlation with catecholamines and cortisol - Ortega Rincon, E.; Marchena, J. M.; Garcia, J. J.; Schmidt, A.; Schulz, T.; Malpica, I.; Rodriguez, A. B.; Barriga, C.; Michna, H.; Lötzerich, H. (Journal of Applied Physiology, 2001)
Flow cytometer measurements were made of the basal variations in peripheral blood functional monocytes and granulocytes over the course of a training season (January to November) of a cycling team. Parallel determinations were made of plasma concentration of catecholamines (chromatography) and cortisol (RIA) in a search for neuroendocrine markers. The results showed the greatest phagocytic capacity to occur in the central months (March, May, and July), coinciding with the greatest number and highest level of competitive events with good correlation with a peak in epinephrine during these months (r2 = 0.998 for monocytes and r2 = 0.674 for granulocytes). No good correlations were found between phagocytosis and norepinephrine or cortisol. The highest values for phagocytosis and epinephrine concentration were found in May. These results suggest that blood epinephrine concentration could be a good neuroendocrine marker of sportspeople's phagocytic response.